Case Report of Three Immature Cystic Teratomas in Northern Ghana - E. M. Der; S. Seidu (Case Reports in Obstetrics and Gynecology)
Background. Preoperative diagnosis of immature cystic teratoma can be challenging for clinicians. In this report, we present three cases. Methods. We describe three women aged 10, 20, and 23 years, respectively, who presented with abdominal masses which were diagnosed by abdominal ultrasound as mature cystic teratomas. All women had emergency laparotomy and oophorectomy. Results. Histopathological examination reported these ovarian tumours to be immature cystic teratomas. This case report also provided a brief summary of the clinicopathological features of all ovarian teratomas diagnosed in two centres during the period of review. Conclusion. Immature ovarian teratoma affects primarily younger patients; it is important for clinicians to have a high sense of suspicion whenever the diagnosis of a germ cell tumour is entertained.